2002
DOI: 10.1007/s12043-002-0079-3
|View full text |Cite
|
Sign up to set email alerts
|

L X-ray energy shifts and intensity ratios in tantalum with C and N ions — multiple vacancies in M, N and O shells

Abstract: The energy shifts and intensity ratios of different L X-ray components in tantalum element due to 10 MeV carbon and 12 MeV nitrogen ions are estimated. From the observed energy shifts, the possible number of simultaneous vacancies in M shell are estimated. A comparison of L α /L β 2 15 , L β1 /L γ1 and L γ2 3 /L γ4 4 with the ratios due to Scofield theoretical transition rates indicate that the number of multiple vacancies in N shell are higher than the vacancies in M and O shell. Employing Larkin's statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In the energy range that overlaps with our present work for C → Pt and Au, following Berinde et al [20], Semaniak et al [15] derived the probabilities for ionization of M and N subshells from changes in relative L x-ray peak yields once protons were replaced with carbon ions. While, with Larkins scaling [21] to deduce the number of multiple vacancies from energy shifts and relative intensities redistribution, this approach evolved into a standard procedure [22], Pajek et al [23] demonstrated that changes in both position and width of x-ray peaks are the most reliable determinants of the outer-shell ionization probabilities.…”
Section: Extraction Of X-ray Production and L-subshell Ionizationmentioning
confidence: 99%
“…In the energy range that overlaps with our present work for C → Pt and Au, following Berinde et al [20], Semaniak et al [15] derived the probabilities for ionization of M and N subshells from changes in relative L x-ray peak yields once protons were replaced with carbon ions. While, with Larkins scaling [21] to deduce the number of multiple vacancies from energy shifts and relative intensities redistribution, this approach evolved into a standard procedure [22], Pajek et al [23] demonstrated that changes in both position and width of x-ray peaks are the most reliable determinants of the outer-shell ionization probabilities.…”
Section: Extraction Of X-ray Production and L-subshell Ionizationmentioning
confidence: 99%
“…e enhancement of ratios of Lι to Lα to the atomic data in Figure 3 indicates directly the multiple ionization in M 4,5 shells, and the diminished trend denotes that the extent of that multiple ionization decreases with the increase of proton energy. For example, the average number of multiple vacancies in M 4,5 shells is estimated using the relationship between the experimental ratios of Lι to Lα and the theoretical values [20,21,30,31]. at is about 5.6 ± 0.8, 5.1 ± 0.7, 4.8 ± 0.7, 4.4 ± 0.6, 3.8 ± 0.5, 4.1 ± 0.6, 4.0 ± 0.6, and 4.1 ± 0.6 for 49 Cd and 6.1 ± 0.9, 4.8 ± 0.7, 4.2 ± 0.6, 4.0 ± 0.6, 3.9 ± 0.5, 3.9 ± 0.5, 3.8 ± 0.5, and 3.8 ± 0.5 for 49 In, with the proton energy of 75, 100, 125, 150, 175, 200, 225, and 250 keV, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a comparison of the fluorescence parameters with theoretical estimates provides a check on the validity of various physical parameters in the evaluation of theoretical estimation [4]. When looked at the literature, the L X-ray intensity ratios of the samples have been studied by a number of researchers using different detectors and sources [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%